Distribución y densidad de la trucha Oncorhynchus mykiss (Salmoniformes: Salmonidae) en los Andes venezolanos - Péfaur, Jaime E (Universidad de Costa Rica, 1998)
Spatial distribution and relative abundance of wild rainbow trout populations were studied in 68 stations located between 500 and 4000 masl in seven hydrologica1 basins of tbe most important Andean rivers of Venezuela during a year of sampling. A total of 6 12 individuals were obtained aboye 1700 m, Most fishes were obtained from tbe Chama (43%),M otatán (21% ) and Santo Domingo (32%) rivers,v ery few in the Negro ( 1.75%) and La Grita (0,33%) rivers,a nd none in tbe Escalante and Mocotíes rivers basins. Adult males were more abundant than females in a 2.15: 1 proportion. Juveniles made a 56.7% of captures,w itb a proportion of 1.30 juveniles per adult, Individual sizes varied from 2.0 to 21.8 cm,m ost within tbe interval 5.1 - 10.0 cm; tbe weight of specimens also showed an ample variation, with a maximum of 317,0 g.